Perceraian Dengan Alasan Murtad(Analisis Putusan Nomor: No. 0396/Pdt.G/2012/PA.Skh di Pengadilan Agama Sukoharjo) - Budiarti, Mustikaningsih Vita; , Mutimatun Ni'ami, S.H., M.Hum; , Ahmad Ridho, S.H (2015)
This study aims to determine the consideration of judges and legal basis Sukoharjo Islamic Court judge in deciding a divorce because one of the apostates and to determine the legal consequences arising from divorce because one of the parties lapsed in Decision No. 0396/Pdt.G/2012/PA.Skh in the Sukoharjo Islamic Court. This research method using the normative method of discussion with how to interpret and discuss the data and processed based on the norms of law, legal doctrine and theory of jurisprudence.. Kind of research is explanatory which provide an explanation about situations, events or facts that occur in the field. Conclusion of the study is that the verification process has been proven legally and convincingly that the Defendants out of the religion of Islam (apostates and their religion back to its original (Christian) religious activities and frequently follow in the church, therefore the Plaintiff assessed has fulfilled the requirements of Article 116 Letter (h) Compilation of Islamic Law. So therefore Plaintiff deserves to be granted, while for some of the legal consequences arising from a divorce, namely breaking the bond of marriage, the enactment of the prescribed period for women, child custody and child living given by the husband to children The adult and can take care of themselves (21 years) as well as the division of joint property is divided in accordance with the provisions as mentioned in Article 96 and 97.